Pengaruh ROA, ROE, dan EPS terhadap Harga Saham pada Industri Barang Konsumsi Non-Siklis yang Terdaftar di Bei Pada Tahun 2021-2023 - Monica, Cassia; Setiawan, Amelia; Djajadikerta, Hamfri (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to determine the extent of the influence of Return on Assets, Return on Equity, and Earnings per Share both simultaneously and partially on stock prices in Non-Cyclical Consumer Goods Industry companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. This type of research is quantitative, with data processing using classical assumption tests and multiple linear regression analysis. The sampling method used is purposive sampling, and 20 companies were selected. The data for these companies were obtained from financial statements on the IDX website and stock closing prices from the Yahoo Finance website for the period 2021-2023. The study results indicate that the variable Return on Assets does not influence stock prices, and the same applies to Return on Equity. However, Earnings per Share does have an impact on stock prices. Then, simultaneously, the variables Return on Assets, Return on Equity, and Earnings per Share affect stock prices. For future researchers, it is recommended to boost the quantity of industry samples and incorporate additional independent factors beyond those examined in this study that are associated with stock prices. Keywords: EPS, ROA, ROE, Share Price.